The Abrahamic pilgrimage story in sermons: An ontological-narrative foundation of Asian American life in faith. Issue 1 (April 2016) - Yang, Sunggu
Sang Hyun Lee and many other Asian American scholars have found that the Abrahamic pilgrimage story has been an ontological-narrative backbone of Asian American faith constructs. This article further explores their previous research by suggesting three distinct theological narrative styles of the given Abrahamic pilgrimage saga: the allegorical-typological narrative style, the illustrative narrative style, and the eschatological-symbolic narrative style. However, though distinct, the styles are closely associated with one another. I will show sermon excerpts by Asian American preachers that are good examples of the theological-spiritual embodiment of the three styles.